Pengaruh Pemberian Masker Seledri (Apium Graveolens L.) Terhadap Pengurangan Jumlah Lesi Jerawat: The Effect of Giving Celery Masks (Apium Graveolens L.) on Reducing The Number of Acne Lesions - Maya Septriana; Rini Hamsidi; Myrna Adianti; Erikha Magdalena Sjioen; Arifa Mustika; Edith Frederika Puruhito; Dwi Setiani Sumardiko; Ario Imandiri (Fakultas Farmasi Universitas Halu Oleo, 2023)
Acne is a skin disease that is common in teenagers. In Indonesia, acne occurs around 85-100% of cases. According to the records of the Indonesian cosmetic dermatology study group, it was shown that 60% of acne sufferers in 2006, 80% in 2007 and 90% in 2009. A face with acne is an image that is not ideal for a teenager and creates dissatisfaction, causing a feeling of lack of self-confidence. One way that can be used to overcome the problem of acne is by giving a celery mask (Apium graveolens L.). Masks are cosmetic preparations for facial skin care which have the benefit of curing acne and acne scars. Celery (Apium graveolens L.) has been shown in several studies to have anti-inflammatory and antibacterial activity to prevent acne. This study aims to prove the effect of using a celery mask to reduce the number of acne lesions. The method chosen in this study was the Pretest-Posttest Control Group Design, by comparing the difference in reducing the number of acne lesions from the celery mask treatment with the paired T-test formula. The results obtained from giving celery masks to 10 young women aged 16-18 years with the classification of mild, moderate and severe acne for 2 weeks showed a significant decrease in the number of acne lesions (p = 0.00). So it can be concluded that giving celery masks can reduce the number of acne lesions in young women aged 16-18 years.